O contrato de trabalho e a previdência privada - Tanaca, Priscila (2006)
The following masters lecture has the purpose of analyzing voluntary, private pension funds and how they are not a part of an employment contract. Before getting into this specific matter, it is necessary to analyze pension funds generally, as part of the social security system. Although they are both part of the social security system, the government pension program and voluntary, private pension funds have distinct characteristics. The government pension program is characterized by mandatory membership and compulsory contributions, imposed by law, regardless of the will of the employer and employee. Voluntary, private pension funds are governed by a legal contract, constructed independently and based on the will of the parties and independent of the rules of the government pension program. Although they each have their own characteristics, voluntary, private pension funds have the same purpose as the government pension program, that is to provide financial security to individuals and to the community. The operation of the voluntary, private pension funds is shared between what we call closed and open entities. The purpose of this lecture is to study the closed entities, including their legal nature, characteristics and the relationship between the parties involved in this legal contract. To analyze these voluntary, private pension funds carried on by the closed entities, we will first consider the general aspects and elements of a legal contract, and then move to the specific elements of a private pension funds contract and an employment contract. When analyzing the nature of an employee s wage, we will learn that contributions to an employee s private pension fund should not be considered a part of the employee s salary. Therefore, it should not be considered as part of the employment contract, neither by legal doctrine nor by judges when making their decisions. The purpose of this scientific research is to establish that there is no relationship between contributions to voluntary, private pension funds and the employment contract, which may stimulate employers to offer participation in voluntary, private pension funds to their employees